Avaliação da sarcopenia, do estado nutricional e da qualidade de vida como preditores de sobrevida em pacientes em tratamento oncológico paliativo - Destri, Rafaela Tonin [UNIFESP] (2019)
Introduction: Malnutrition is very common in patients undergoing palliative cancer treatment. When there is a reduction in muscle mass, strength and / or function is considered sarcopenia. Tools for assessing nutritional status, sarcopenia and quality of life enable early interventions to be performed, thus contributing to a better quality of life and prognosis. Objective: To associate nutritional status, quality of life and sarcopenia with survival in patients with digestive tract tumor undergoing palliative chemotherapy. Method: Prospective longitudinal study, performed at the UNIFESP oncology outpatient clinic from December 2017 to February 2019 in patients with digestive system cancer undergoing palliative chemotherapy. Three evaluations were performed (T1 to T3) including the subjective subjective assessment produced by the patient, the quality of life questionnaire (EORTC-QLQ-C30) and the bioimpedance phase angle (PA) (BIA). For the diagnosis of sarcopenia, the EWGSOP2 criteria were used, in which muscle strength was measured by dynamometry test, muscle mass by BIA and computed tomography (CT) and physical performance assessed by gait speed test. Results: We included 57 patients, mean age 62 years, male predominance and colorectal cancer. There was a prevalence of malnutrition in 86%, sarcopenia in 75% and impaired quality of life in 75% of the T1 group, with gradual worsening for each parameter until T3. Muscle mass by BIA showed a positive correlation with CT. PA was <5 ° in 84% of patients, but was not statistically relevant with survival. Patients with severe malnutrition, sarcopenia and moderate weight loss had survival <10 years. Conclusion: Severe malnutrition, moderate weight loss and sarcopenia compromised the quality of life and were predictive factors of shorter survival.